Upaya Meningkatkan Hasil Belajar Matematika Materi Bangun Ruang Menggunakan Media Kongkret pada Siswa di MIN 1 Gunungkidul - Setyowati, Lilik (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to identify improvements in learning outcomes of building space using concrete media. The subjects of the study were grade IV students of MIN 1 Gunugkidul in the 2023/2024 Academic Year totalling 18 students. The instruments used are tests that have been validated by experts, observations in accordance with content standards, and documentation. Data analysis techniques use qualitative analysis and quantitative analysis. The results of this study showed that there was an increase in students' scores of building space material before and after being given action with an average score of 79.6 in cycle I, and 83.2 in cycle II. The percentage of completeness is 63% in cycle I, and 87.06% in cycle II. The application of concrete media can improve mathematics learning outcomes of simple room building materials for grade IV MIN 1 Gunungkidul students.